2009
DOI: 10.1063/1.3064162
|View full text |Cite
|
Sign up to set email alerts
|

Pt/Co/oxide and oxide/Co/Pt electrodes for perpendicular magnetic tunnel junctions

Abstract: This letter presents a study of perpendicular magnetic anisotropy in oxide/Co/Pt structures, which could constitute the upper magnetic electrode of magnetic tunnel junctions. The growth of cobalt layers on SiO2 substrates shows that all 0.6 nm thick Co films are superparamagnetic, whereas perpendicular magnetic anisotropy is obtained for 1.5 nm films after annealing. Co layers grown on various Al and Mg oxides prepared by sputtering also exhibit perpendicular magnetic anisotropy after annealing. Combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 16 publications
6
84
1
Order By: Relevance
“…For the thinnest magnetic layers (0.4 nm), is 40 mT in the case of Co and 4 mT in the case of CoFeB. The order of magnitude difference is similar to [10].…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…For the thinnest magnetic layers (0.4 nm), is 40 mT in the case of Co and 4 mT in the case of CoFeB. The order of magnitude difference is similar to [10].…”
Section: Resultssupporting
confidence: 53%
“…These layers do not induce a strong interfacial anisotropy, like Pt or Pd, in the as-deposited state. Nevertheless, Nistor et al recently demonstrated that it is possible to stabilize PMA in thin layers of CoFeB grown on a buffer layer of MgO capped by Pt after annealing at 350 [10]. It has also been shown that with high temperature annealing, it is possible to stabilize PMA with underlayers and this is attributed to the hybridization of the Co and O orbitals after high-temperature annealing [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nistor et al 8 report on SiO 2 \Co\Pt trilayers and conclude that annealing can modify the magnetic anisotropy of Pt capped Co thin films deposited on an amorphous template from in-plane to perpendicular. The HfO 2 \Co\Pt trilayers reported here show the same annealing behaviour (although for lower annealing temperatures), which can similarly be ascribed to the amorphous nature of HfO 2 .…”
Section: B Magnetic Characterizationmentioning
confidence: 99%
“…4 HfO 2 on the other hand is amorphous. Co\Pt bilayer structures have already been studied on other amorphous oxides like SiO 2 by Nistor et al 8 They report that an annealing temperature from 250 C to 400 C can modify the Magnetic Anisotropy (MA) of a thin Co film from in-plane (IP) to perpendicular (PMA). The oxygen atoms at the interface between Co and the oxide may also contribute to the appearance of PMA, through hybridization of the Co 3 d z orbitals with the oxide 2p xy(yz) orbitals.…”
Section: Introductionmentioning
confidence: 99%
“…Hysteresis loop of the F3-film was also measured ex-situ under higher applied magnetic field and is given in fig.1 It is important to note that hybridization is localized at the interfaces and therefore, even with oxygen mediated interfaces (as mentioned above), significant PMA is observed only in ultra thin magnetic layer ranging from fewÅ to a few tens ofÅ. 8,9 In the present work, PMA in 104Å thick Co layer is some what surprising and can not be understood only in-terms of interface hybridization.…”
mentioning
confidence: 98%